Social and health considerations on older British immigrants in Spain, particularly those of the Sunshine Coast - Betty, Charles; Cahill, Michael (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This paper attempts to identify key issues which bear upon the experience of migration by older British expatriates to the Costa del Sol. An analysis is given which attempts to describe the pattern and aspects of migration. It also focuses on the influence of tourism on migration; the perceived necessity of establishing friendship and social network patterns; problems of identity, the lack of coping language and its effect on integration into local Spanish society. Self imposed exclusion is explored by the formation of expatriate social clubs. An examinations is also made of the provision of Spanish health care for older British retirees, and the problems of adequate after care, and the implications of modern Spanish family structures for the Spanish care system. These issues are being explored in an ongoing study of the older British expatriate community in Benalmadena in Southern Spain.